Implementasi Nafkah Anak Pasca Perceraian di Kota Jambi (Tinjauan Undang-undang Nomor 23 Tahun 2002) - Ansori, Muhammad; Sulaiman, Iffan (Jurnal Kridatama Sains dan Teknologi, 2022)
The writing of this scientific paper is to find out the obligations that must be fulfilled by parents (fathers) to their children after a divorce, such as the obligation to provide a living for their children in the form of living expenses, school fees, and so on which are borne by their parents. Because from the data that the author got from observations and interviews in the field, especially in the city of Jambi, there are still many parents (fathers) who do not fulfill their obligations to provide for their children after divorce from their wives of course, this deviates from the provisions of juridical law in Indonesia which burdening parents (fathers) to provide for their children after divorce. The method used in this study is qualitative, while the approach used in this study is a sociological juridical approach. From this study, the author can conclude several points: 1) the causes of non-fulfillment of obligations to children after parents divorce are: First, because of economic factors. Second and third, because the ex-husband has remarried, so he forgets the responsibility to provide for his children after the divorce; 2) Review of Law Number 23 of 2002 Articles 2 and 12 on the Fulfillment of Children's Livelihoods after Divorce in Jambi City: Child protection is all activities to provide guarantees, protection, and rights so that they can live, grow, develop, and participate actively optimally by human dignity, as well as getting protection from violence and discrimination. Keywords: Child Custody, Divorce, and the Act.